The directs costs of A-REIT IPOs. Issue 2 (2nd March 2015) - Dimovski, Bill
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Direct costs of Australian Real Estate Investment Trust (A-REIT) initial public offerings (IPOs) were last reported in the literature using data to 2004. Much has occurred since then. The purpose of this paper is to introduce and include the A-REIT IPOs over the last ten years and examine the cost and the factors influencing the percentage underwriting and percentage total direct costs by A-REITs IPOs. The study also investigates specifically whether the utilization of an underwriter (who guarantees the success of the capital raising) rather than a stockbroker (who does not guarantee such success) costs significantly more. Design/methodology/approach – The study examines 87 A-REIT IPOs from January 1994 until December 2013. An OLS regression is performed to identify significant influencing factors on percentage underwriting costs and percentage total direct capital raising costs. Findings – The study finds that larger capital raisings and those with large investor or institutional involvement identified in the prospectus are significant in reducing underwriting costs. The study does not find that underwritten IPOs are significantly more expensive (or cheaper) than those not underwritten. Additionally, the size of the issue, whether the firm offers stapled securities (is internally managed) and has higher net asset to issue price characteristics reduces the total cost of underwritten IPOs. Practical implications – The paper provides information to new A-REIT issuers, underwriters and advisors broadly on new issue costs and on factors influencing the IPO issue costs. Originality/value – The study is the first to examine the costs of A-REIT IPO capital raising data in the years prior to and following the recent global financial crisis period.